Asuhan Kebidanan Pada Ibu Hamil Dengan Hipertensi Gestasional Di PMB Husnel Hayati Wilayah Kerja Puskesmas Salo 2023 - Fitrah, Elza; Syahda, Syukrianti; Ariesta, Marini (Evidence Midwifery Journal, 2024)
Gestational hypertension is one of the problems in pregnancy. Mothers with gestational hypertension will have adverse effects on themselves and the fetus they are carrying, including low birth weight (LBW), neonatal asphyxia, and intrauterine fetal growth retardation (IUGR). The purpose of the study was to provide Midwifery Care for Pregnant Women with Gestational Hypertension at PMB Husnel Hayati, Salo Health Center Working Area in 2023. This study uses a descriptive observational research design with a case study approach to study midwifery care, namely research that describes and interprets something, such as existing conditions or relationships, developing opinions, ongoing processes, consequences and effects that occur, or ongoing trends. In this study, the assessment and collection of basic data were carried out using SOAP with Varney's thought pattern, namely subjective assessment, objective assessment, analysis and then management according to the problems experienced by Mrs. D, namely pregnant women with gestational hypertension. After an evaluation was conducted to analyze the patient's response to the intervention that had been given. The study provided care to the mother, namely consuming carrot juice for 7 consecutive days, reducing salt intake, consuming a balanced diet and implementing every recommendation and health education given by health workers so that the mother's blood pressure could return to normal.